A Review of the Global Polygonal Faults: Are They Playing a Big Role in Fluid Migration? - Xia, Ying; Yang, Jinxiu; Chen, Yong; Lu, Shuangfang; Wang, Min; Deng, Shaogui; Yao, Zhiguang; Lu, Mingyue (Frontiers in Earth Science, 2022)
Polygonal faults (PFs) have been widely found in over 100 sedimentary basins worldwide, mainly in marine setting on continental margins and intracratonic sedimentary basins. PFs are characterized by layer-bound minor normal faults arranged in polygonal patterns and multi-direction strikes, most of which were developed in fine-grained sediments rich in claystone. The genesis mechanisms of PFs have been recognized as non-tectonic, mainly including shear failure, syneresis, density inversion, low coefficients of friction and gravity sliding theory. Previous studies often regarded PFs as conduits playing a role in favouring fluid migration, which were also regarded as fluid source expelled during PF generation. However, some researchers proposed that the PF-bearing layer is generally impermeable and may act as a seal. To better understand the role of PFs in fluid migration and their contrition to the shallower hydrocarbon accumulation, a geophysical review of global PFs case studies is conducted in this paper. A comprehensive analysis is carried out based on abundant case studies, with key parameters analyzed including the PFs characteristics (e.g. buried depth, lithology, size, etc.), formation mechanisms of PFs, tectonic-sedimentary setting, and the spatial relationship of PFs, nearby major fluid migration pathways and high amplitude anomalies. The compilation of global PF case studies of shows that hydrocarbon fluids from the deep is more likely to migrate upward through normal big faults, gas chimneys or unconformities surface around PFs. In most cases, PFs play limited roles in fluid migration, such as in South China Sea where hydrocarbon accumulations have been observed under the PFs and the PF-bearing layer may act as a seal trapping the free gas underneath. Generally, the role of PFs in fluid migration should be determined through a comprehensive analysis of the characteristics of PFs, surrounding amplitude anomalies, hydrocarbon distribution, and even the sealing ability of PFs which needs further study. It is more likely that the PFs play a limited role in vertical fluid migration and related shallower hydrocarbon accumulation and distribution.